Peran Media Massa Surat Kabar terhadap Pengaruh The Beatles dalam Perkembangan Musik Indonesia Tahun 1970–2000 - Siti Nur Aulia; Mahbub Hefdzil Akbar; Fathia Lestari (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This study aims to analyze the strategic role of newspapers in introducing and reinforcing the influence of The Beatles on the development of popular music in Indonesia from 1970 to 2000. Utilizing a historical research method with a descriptive-analytical approach, the study underwent four main stages: heuristics, involving the collection of primary sources such as newspaper archives from Kompas, Bali Post, and What’s On; source criticism for data validation; interpretation to analyze data correlations; and historiography to synthesize a systematic historical narrative. Additionally, the study employs Antonio Gramsci’s theoretical framework of hegemony to dissect how mass media functions as a cultural production tool that builds